Bridge between Faith and Neutrality: MDMC’s Humanitarian Diplomacy in the Era of Global Funding Crisis - Musfiroh; Faisal (Dauliyah Journal of Islamic and International Affairs, 2026)
Amid escalating global humanitarian crises and severe financial deficits facing multilateral institutions, Faith-Based Organizations (FBOs) have emerged as crucial actors in bridging the international aid gap. This study analyzes the humanitarian diplomacy strategies employed by the Muhammadiyah Disaster Management Center (MDMC) across two complex conflict zones: Gaza and Myanmar. Utilizing Robert K. Yin’s (2018) qualitative multi-case study design alongside data analysis procedures from Miles, Huberman, and Saldaña (2014), this research investigates how MDMC navigates the inherent tension between internal religious identity and external professional demands. Drawing upon Petersen’s (2012) typology of transnational Islamic organizations, the findings reveal that MDMC executes a dynamic tactical synthesis of proselytization motives (embedded values) and professional field practices (enacted neutrality). Specifically, MDMC operationalizes the theological concept of rahmatan lil-‘alamin into universal protocols through World Health Organization Emergency Medical Team (EMT) certification. Furthermore, MDMC leverages strategic partnerships with local champions to overcome bureaucratic impediments and logistical access constraints in highly sensitive regions. By synergizing Muhammadiyah's financially autonomous internal network with global external partnerships, MDMC effectively mitigates vulnerabilities in international funding. Ultimately, this study concludes that this autonomous diplomacy model not only guarantees sustainable, objective aid delivery amid widespread international budget cuts, but also significantly reinforces Indonesia’s non-state humanitarian diplomacy posture on the global stage.